2022
DOI: 10.3390/ijms23084089
|View full text |Cite
|
Sign up to set email alerts
|

Possible Repositioning of an Oral Anti-Osteoporotic Drug, Ipriflavone, for Treatment of Inflammatory Arthritis via Inhibitory Activity of KIAA1199, a Novel Potent Hyaluronidase

Abstract: KIAA1199 has a strong hyaluronidase activity in inflammatory arthritis. This study aimed to identify a drug that could reduce KIAA1199 activity and clarify its effects on inflammatory arthritis. Rat chondrosarcoma (RCS) cells were strongly stained with Alcian blue (AB). Its stainability was reduced in RCS cells, which were over-expressed with the KIAA1199 gene (RCS-KIAA). We screened the drugs that restore the AB stainability in RCS-KIAA. The effects of the drug were evaluated by particle exclusion assay, HA E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 40 publications
0
6
2
Order By: Relevance
“…In a previous study, ipriflavone showed the ability to suppress KIAA1199 activity and inhibited HA depolymerization in fibroblast-like synoviocytes (FLSs) stimulated with TNFα, whereas in the present study, ipriflavone reduced the protein expression of KIAA1199 in the OA cartilage [19]. The mechanism by which ipriflavone directly suppresses KIAA1199 protein expression is unknown.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In a previous study, ipriflavone showed the ability to suppress KIAA1199 activity and inhibited HA depolymerization in fibroblast-like synoviocytes (FLSs) stimulated with TNFα, whereas in the present study, ipriflavone reduced the protein expression of KIAA1199 in the OA cartilage [19]. The mechanism by which ipriflavone directly suppresses KIAA1199 protein expression is unknown.…”
Section: Discussioncontrasting
confidence: 53%
“…The results of this study revealed that ipriflavone, which was shown to inhibit KIAA1199 [19], could inhibit cartilage degradation in a mouse OA model with DMM surgery. In addition, the inhibitory effects of ipriflavone were confirmed by the results of the bovine cartilage explant culture under IL-1β stimulation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Therefore, CEMIP may have a positive correlation with MMP2, MMP7, MMP13, and MMP14 and regulate tumor cell EMT through MMPs to promote tumor cell migration. Koike et al (9) reported that ipriflavone can be a drug that inhibits the hyaluronidase activity of CEMIP and inhibits the expression of MMP1 and MMP3 in FLS cells stimulated by TNF-a.…”
Section: Cemip and Ecmmentioning
confidence: 99%
“…Abnormal expression of CEMIP can also regulate non-neoplastic diseases, such as inflammation and infection. Studies have shown that the anti-CEMIP monoclonal antibody (anti-CEMIP), ipriflavone, and paclitaxel (PTX) combined with the latest nanosphere-targeted drug delivery technology can make CEMIP as a therapeutic target to inhibit inflammation or tumor development (9,10).…”
mentioning
confidence: 99%